The Effect of Anti-anxiety Medication on Recall Performance of Happy Memories Using the 2k Factorial Design Method - Utami, Rahmi; Sofro, Ayunin (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2024)
Anxiety disorders are common mental health problems and can significantly impact a person's quality of life. This study aims to examine the effect of anti-anxiety drugs, especially benzodiazepines, on individuals' ability to remember happy memories. The research method used was a 2k factorial design to identify interactions between the factors tested, namely drug A, drug T, and drug S (a representation of benzodiazepine drugs) at two different levels. The data is analyzed quantitatively by utilizing values ​​that have been taken from the Kaggle application. This research was conducted by paying attention to the effect of anti-anxiety drugs on happy memory performance, taking into account the effects of dose, duration of use, and individual response to the drug. The 2k factorial design makes it possible to understand the interactions between the factors and how they influence the observed response. The research results obtained are the effect of the drug Triazolam is the only one that can be used to increase the influence/effect on the user's memory performance of happy memories. Apart from that, using the p-value in ANOVA (Analysis of Variance) you can find out that the main effect is statistically significant and that there is no interaction between these factors. This confirms my initial interpretation of the data based on the magnitude of the factor influence. After conducting ANOVA (Analysis of Variance, the regression results show A2, T2, and S2 (factors at dose 2) have a significant influence on the dependent variable (happy memory recall performance). Keywords : anxiety disorders, benzodiazepines, happy memory recall, 2k factorial design, anxiety treatment